STRATEGI PENGELOLAAN PERTANIAN LAHAN KERING DALAM MENINGKATKAN KETAHANAN PANGAN DI NUSA TENGGRARA TIMUR - Rupa Matheus; M. Basri; Mika S. Rompon; Nimrod Neonufa (Politeknik Pertanian Negeri Kupang, 2017)
Strategy of dryland farm management in improving food security in East Nusa Tenggara; One of the promising opportunities but often to be neglected is the use of arable dryland suitable for food crops production, The potential of available dryland agroecosystems is quite extensive and technically suitable for agriculture. The potential land will be able to produce sufficient food if managed using effective technology and appropriate development strategies. Strategies for utilizing potential dry land are: 1) emelioration measures to improve soil quality by utilizing in-situ local resources 2) increased land productivity and sustainable commodity production of dry land sustainably, and 3) rain harvesting Â technology, and 4) improvement of economic infrastructureKeywords: Dryland, land management strategy, food security